2020
DOI: 10.1136/bmjopen-2020-039576
|View full text |Cite
|
Sign up to set email alerts
|

Occupational noise-induced hearing loss in China: a systematic review and meta-analysis

Abstract: ObjectiveMost of the Chinese occupational population are becoming at risk of noise-induced hearing loss (NIHL). However, there is a limited number of literature reviews on occupational NIHL in China. This study aimed to analyse the prevalence and characteristics of occupational NIHL in the Chinese population using data from relevant studies.DesignSystematic review and meta-analysis.MethodsFrom December 2019 to February 2020, we searched the literature through databases, including Web of Science, PubMed, MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 44 publications
3
69
0
7
Order By: Relevance
“…It is considered the most prevalent work-related disease worldwide, affecting more than 10% of all workers in developed countries [18]. A recent systematic review from China estimated a prevalence of 21.3% for occupational NIHL in noise-exposed Chinese workers over the last 26 years [19]. A similar figure was calculated for workers in the USA: there, the prevalence of hearing loss in noise-exposed workers was about 20% between 1981 and 2010.…”
Section: Epidemiology Of Nihl-international Comparisonmentioning
confidence: 77%
“…It is considered the most prevalent work-related disease worldwide, affecting more than 10% of all workers in developed countries [18]. A recent systematic review from China estimated a prevalence of 21.3% for occupational NIHL in noise-exposed Chinese workers over the last 26 years [19]. A similar figure was calculated for workers in the USA: there, the prevalence of hearing loss in noise-exposed workers was about 20% between 1981 and 2010.…”
Section: Epidemiology Of Nihl-international Comparisonmentioning
confidence: 77%
“…Noise induced hearing loss is a common disorder that has many health consequences [1][2][3][4]. NIHL has many health consequences ranging from auditory processing deficits, attention and cognitive loss to social isolation.…”
Section: Resultsmentioning
confidence: 99%
“…Up to 7% of noise induced loss in Australia has been found to arise from occupational noise [3]. Zhou, Shi, Zhou, Hu, and Zhang [4] reported that the prevalence of NIHL in Hungary was 21.3%, with 30.2% was related to high frequency NIHL. Thus, NIHL occurs with regularity in many world societies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One retrospective study that recruited 76 participants (34 helicopter pilots and 42 aircraft mechanics) from the Thai Army also reported that aircraft mechanics suffered from damage to the hearing frequencies involved in speech and high frequencies and a greater decibel loss than the aviators [ 31 ]. The difference of noise impact on hearing between ground staff and pilots may reflect several factors, such as the use of hearing protection [ 31 , 32 ], the participant’s smoking status [ 31 , 33 ], the duration of occupational noise exposure, and co-exposures to non-occupational noise or specific chemicals such as organic solvents, welding fumes, carbon monoxide, and hydrogen sulfide [ 34 , 35 , 36 ]. We also speculate that sonic booms (the sound associated with the shock waves) usually lag behind the aircraft; therefore, the most unbearably loud noise would be encountered by the ground staff, who may spend a further consecutive hour working in the hardened aircraft shelter, either close to or 7 m away from the aircraft, as they conduct the outside inspection and checks before the fighter aircraft leaves the shelter for the runway.…”
Section: Discussionmentioning
confidence: 99%